Virtual Reality Applications for Interactive Tourism : A New Era of Engagement - Adebayo Ogunleye; Ibrahim Abubakar; Usman Musa (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Virtual reality (VR) is revolutionizing the tourism industry by offering immersive experiences that engage users before, during, and after their trips. This paper discusses the potential of VR in virtual tours, heritage preservation, and destination marketing. The findings highlight the benefits of VR in increasing destination appeal, reducing physical limitations, and promoting cultural awareness.